2011
DOI: 10.1038/hr.2011.79
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is diagnosed as a sustained elevation of pulmonary arterial pressure to more than 25 mm Hg at rest or to more than 30 mm Hg with exercise. PAH is an intrinsic disease of the pulmonary vascular smooth muscle and endothelial cells in association with plexiform lesions, medial thickening, concentric laminar intimal fibrosis and thrombotic lesions. Pulmonary vascular remodeling is the characteristic pathological change of PAH. The pathogenesis of PAH has been studied at the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…It is characterized by elevated pulmonary arterial pressures (PAP), and increased pulmonary vascular resistance leading to right-sided heart failure and death [1], [7]. Evidence reveals that epigenetic alterations may be involved in PAH such as changes in the phenotype or in gene expression states, including chromatin remodeling, DNA methylation and histone modifications [28]. The importance of EZH2 in the proliferation of HPASMCs and its implications in the development of PAH is demonstrated for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by elevated pulmonary arterial pressures (PAP), and increased pulmonary vascular resistance leading to right-sided heart failure and death [1], [7]. Evidence reveals that epigenetic alterations may be involved in PAH such as changes in the phenotype or in gene expression states, including chromatin remodeling, DNA methylation and histone modifications [28]. The importance of EZH2 in the proliferation of HPASMCs and its implications in the development of PAH is demonstrated for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Recently identified race-and sex differences in the effects of ERA therapy in PAH patients (Gabler et al, 2012), ERA-drug interactions (Venitz et al, 2012) (Pulido et al, 2009;Srinivas, 2009;Walker et al, 2009;Harrison et al, 2010;Spangler and Saxena, 2010), and epigenetic regulation in PAH (Xu et al, 2011) require further clinical research.…”
Section: Current Perspectives For Era Therapy In Clinical Medicinementioning
confidence: 98%
“…However, the increased eNOS expression did not completely offset the effect of vasoconstrictors, such as endothelin-1 (ET-1), and subsequent development of PPHN [19,20]. A number of clinical studies demonstrated that increased ET-1 was strongly associated with PAH [21-23].…”
Section: Introductionmentioning
confidence: 99%